Preparation method of TTA photonic crystal

By embedding TTA-pdma in TTA photonic crystals using photonic crystal band edge effect and self-assembly method, a photonic crystal with enhanced blue light emission is formed, which solves the problem of low photocatalytic efficiency in the prior art, and achieves efficient photocatalytic effect, which is suitable for a variety of optical applications.

CN119507023APending Publication Date: 2025-02-25HAIYING ENTERPRISE GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411673069.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the photocatalytic efficiency of TTA photonic crystals, and there is a lack of suitable preparation methods to meet the needs of production and life.

Method used

By utilizing the photonic crystal band-edge effect, PS spheres with different ratios were prepared by soap-free emulsion polymerization, and TTA-pdma was embedded on the surface of the hollow SiO2 crystal thin film by self-assembly method, and then cured by photopolymerization to form a photonic crystal with enhanced blue light emission.

Benefits of technology

The Faraday efficiency of the photocatalyst CdS-Au has been improved, from 40% to more than 90%, and the high-energy photon emission capability of photonic crystals is enhanced. It is suitable for optical communications, photonic integrated circuits and solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507023A_ABST
    Figure CN119507023A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a TTA photonic crystal, which is characterized in that exciting light of TTA up-conversion is enhanced by utilizing a photonic crystal band edge effect, so that high-energy photons are structurally enhanced, an SEM (scanning electron microscope) graph of five groups of prepared PS (polystyrene) spheres with different diameters is analyzed, silicon dioxide prepared by a modified Stober method is used as a shell, and the structure of the shell is enhanced. And preparing to obtain PS-coated SiO2 monodisperse colloid particles, thereby completing SiO2 coating. And carrying out high-temperature treatment to obtain the hollow SiO2 photonic crystal film. The photocatalyst CdS-Au is prepared, and the photocatalyst CdS-Au is washed and dried. The theoretical PS sphere diameter is finally confirmed to be 245 nm through FDTD simulation, the SiO2 shell layer thickness is 20 nm, and through electron microscope analysis, the PS sphere with the styrene-PVP ratio being 8-0.5 and most conforming to the FDTD simulation result is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical environmentally friendly materials, and in particular to a method for preparing a TTA photonic crystal. Background Art

[0002] Photonic crystal was independently proposed by S. John and E. Yablonovitch in 1987. It is an artificial microstructure formed by the periodic arrangement of media with different refractive indices. Photonic crystal is a photonic bandgap material. From the perspective of material structure, photonic crystal is a type of artificially designed and manufactured crystal with a periodic dielectric structure on an optical scale. Similar to the modulation of electron wave functions by semiconductor lattices, photonic bandgap materials can modulate electromagnetic waves with corresponding wavelengths. When electromagnetic waves propagate in photonic bandgap materials, they are modulated due to the existence of Bragg scattering, and the energy of electromagnetic waves forms an energy band structure. Band gaps appear between energy bands, namely photonic band gaps. Photons with energy within the photonic bandgap cannot enter the crystal.

[0003] Nowadays, the massive consumption of fossil energy and the rapid development of industry have made human beings face an increasingly deteriorating ecological environment. Photocatalytic technology can use sunlight to remove most toxic and harmful substances, which has a positive significance for solving environmental pollution problems. TTA upconversion has the advantages of low light excitation intensity, adjustable excitation and emission wavelengths, strong absorption and emission, and high upconversion quantum yield, which makes it have a good development prospect. Therefore, it is urgent to design a complete preparation method for TTA to improve the Faraday efficiency and meet the current and future production and life needs. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing a TTA photonic crystal, wherein the preparation method utilizes the band edge effect of the photonic crystal to enhance the excitation light of the TTA upconversion, thereby achieving structural enhancement of high-energy photons, firstly, using a soap-free emulsion polymerization method to prepare PS beads with different ratios, and then preparing the photonic crystal, comprising the following steps:

[0005] Step S1: Gently place a magnetic stirrer in a reaction container, and add 0.1-1 g of initiator, 150 ml of deionized water, 5-9 ml of styrene as a polymerization monomer, and 0.5 ml of PVP as a comonomer in sequence;

[0006] Step S2: Take a balloon with sufficient nitrogen for standby use, then build a complete reaction device with a magnetic stirrer and a reaction vessel, and connect the nitrogen balloon to the inlet of the reaction vessel through a nitrogen pipe, and adjust the nitrogen flow rate;

[0007] Step S3: Turn on the magnetic stirring, set the temperature of the temperature controller at 30°C, stir with nitrogen for 30-45 minutes, then continue to heat up, set the temperature to 75°C, and close the gas outlet to prevent backflow;

[0008] Step S4: After the temperature rises to 75°C, 5 ml of sample is drawn with a disposable syringe, and a small amount of quencher solution (1.0 g / L hydroquinone aqueous solution, 0.5 ml) is added to record the color change of the reaction system. After the reaction is carried out at 75°C for 5-8 hours, heating is stopped;

[0009] Step S5: performing magnetic stirring at room temperature to lower the system temperature to room temperature, and preparing five groups of PS beads with different styrene-PVP ratios;

[0010] Step S6: modifying the prepared PS beads, preparing PS@SiO2 beads, and separating monodispersed PS@SiO2 beads, embedding TTA-pdma into the surface of the hollow SiO2 crystal film by self-assembly again, and then curing it by photopolymerization to obtain a photonic crystal with enhanced blue light emission;

[0011] Step S7: Finally, the photocatalyst CdS-Au is prepared and the sensitization efficiency is measured with the photonic crystal.

[0012] In one embodiment of the present invention, the reaction container is a clean 250 ml three-necked round-bottom flask; a thermometer is provided at one port of the three-necked round-bottom flask for measuring the oil bath temperature, so the set temperature is 3 to 5°C higher than the reaction temperature.

[0013] In one embodiment of the present invention, the nitrogen pipe in step S2 is immersed below the liquid level in the reaction container, and the nitrogen flow rate is adjusted to an appropriate flow rate so that the bubbling rate at the gas outlet is about 1-3 per second; a two-way valve is provided on the nitrogen pipe for controlling the gas flow rate, wherein the gas flow rate is 1-3 per second, and the ventilation is 30-45 minutes.

[0014] In one embodiment of the present invention, the rate of starting magnetic stirring in step S3 is 300 rpm.

[0015] In one embodiment of the present invention, the quencher solution used in step S4 is a 1.0 g / L hydroquinone aqueous solution, 0.5 ml.

[0016] In one embodiment of the present invention, the styrene used in the preparation method will add some acidic inhibitors due to inventory management requirements, so it must be removed before use, that is, a glass tube is used, clean cotton is placed at one end of the pointed outlet of the tube, and then alumina sand is filled, and then the styrene monomer to be filtered is poured in, and the inhibitor is removed by the adsorption effect of alumina.

[0017] In one embodiment of the present invention, the obtained PS beads are modified, including the following: 10 ml of the PS beads obtained in step S5 are taken into a conical flask, 6 ml of ethanol is added, and 4 ml of 10 g / LPVPK30 alcohol solution is added under magnetic stirring, and the mixture is reacted at room temperature for 24 hours, and then centrifuged and washed 6 times with alcohol, and the mixture is dispersed and stored in 9 ml of alcohol for later use.

[0018] In one embodiment of the present invention, the preparation of PS@SiO2 beads comprises the following steps: placing the prepared modified beads in a single-necked flask, adding 4.1 ml of ultrapure water and 0.5 ml of ammonia water, and stirring for 10 minutes;

[0019] Take 0.4 ml of ethyl orthosilicate and disperse it in 36 ml of alcohol. Quickly add it to a single-necked flask and react it at room temperature for 12 hours. Finally, wash it by centrifugation with water and alcohol for 3 times and store it in alcohol for later use.

[0020] In one embodiment of the present invention, the separation of monodisperse PS@SiO2 beads comprises the following steps: placing the PS@SiO2 bead suspension prepared as described above on a vibration-free workbench; after standing for a period of time, removing the upper solution and lower precipitate in the suspension; and monodisperse silica beads can be obtained by extracting the solution in the middle portion.

[0021] Specifically, 0.03g of PS microsphere powder was weighed and dissolved in a mixture of 35mL of anhydrous ethanol and 2mL of deionized water by ultrasonic dispersion. After the PS microspheres were completely dispersed, 0.5mL of ammonia water was quickly added to the system and reacted for 1h under continuous magnetic stirring. Subsequently, different amounts of tetraethyl orthosilicate were added to the system, and magnetic stirring was performed at room temperature (about 30°C in summer) for 8h to obtain a white solution. After centrifugation, water washing, alcohol washing, drying and other processes, white PS@SiO2 powder was obtained.

[0022] In one embodiment of the present invention, the preparation of the photocatalyst CdS-Au includes the following steps: 2.21 g BiCl3 and 1.05 g CTAB are added to 60 mL ethylene glycol, stirred vigorously for 40 min, and then 2.8 g Na3VO4 is added, stirred for 5 min, and the mixture is added to a polytetrafluoroethylene hydrothermal reactor, and reacted at 160° C. for 3 h. The product is washed with water and ethanol 3 times each, and dried in a vacuum for 12 h.

[0023] The above technical solution of the present invention has the following advantages over the prior art: the preparation method of the TTA photonic crystal described in the present invention is to fill TTA-PDMS in the template gap and solidify it to obtain a photonic crystal with enhanced blue light emission; it can effectively sensitize the photocatalyst, thereby achieving the purpose of improving the photocatalytic efficiency, and has a wide range of applications in optical communications, photonic integrated circuits, solar cells, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to make the contents of the present invention more clearly understood, the present invention is further described in detail below based on specific embodiments of the present invention in conjunction with the accompanying drawings.

[0025] Figure 1 The invention discloses a method for preparing a TTA photonic crystal, and obtains a FDTD simulation result of the photonic crystal;

[0026] Figure 2 is a scanning electron microscope image of PS beads obtained by the preparation method of the present invention;

[0027] Figure 3 This is a diagram of the hollow SiO2 lens of the present invention;

[0028] Figure 4 It is an electron microscope image of PS, PS@SiO2, and hollow SiO2 spheres described in the present invention;

[0029] Figure 5 is the transmission spectrum of PS balls with different diameters in the present invention;

[0030] Figure 6 This is a diagram of the CdS nanorod lens of the present invention. DETAILED DESCRIPTION

[0031] Embodiment 1

[0032] The present embodiment provides a method for preparing a TTA photonic crystal. The method utilizes the band edge effect of the photonic crystal to enhance the excitation light of TTA upconversion, thereby achieving structural enhancement of high-energy photons. The method is characterized in that PS beads with different ratios are first prepared by soap-free emulsion polymerization, and then the photonic crystal is prepared.

[0033] Preparation of PS beads

[0034] Use a clean three-necked round-bottom flask (250 ml) as a reaction container, gently place a magnetic stirrer in it, and then add 0.1-1 g of initiator, 150 ml of deionized water, 5-9 ml of styrene as a polymerization monomer, and 0.5 ml of PVP as a comonomer. Take a balloon with sufficient nitrogen for standby use, then set up the reaction device as shown in the experimental requirements, ensure that the nitrogen pipe is immersed below the liquid surface, adjust the nitrogen flow rate to an appropriate flow rate, so that the bubbling rate at the gas outlet is about 1-3 / second, then turn on the magnetic stirring (stirring rate is about 300rpm), set the temperature of the temperature controller at 30℃, after stirring with nitrogen for 30-45min, continue to heat up, set the temperature to 75℃, and close the gas outlet to prevent back suction. After the temperature rises to 75℃, use a disposable syringe to draw 5ml of sample, and add a small amount of quencher solution (1.0g / L hydroquinone aqueous solution, 0.5ml) to record the color change of the reaction system. After the reaction is carried out at 75℃ for 5-8h, stop heating, and carry out magnetic stirring at room temperature to lower the system temperature to room temperature to obtain PS beads;

[0035] Modification of PS beads

[0036] Take 10 ml of the prepared PS beads in a conical flask, add 6 ml of ethanol, add 4 ml of 10 g / LPVPK30 alcohol solution under magnetic stirring, react at room temperature for 24 hours, then use alcohol centrifugation to wash 6 times, disperse and store in 9 ml of alcohol for later use;

[0037] Preparation of PS@SiO2 pellets

[0038] Place the modified beads in a single-necked flask, add 4.1 ml ultrapure water and 0.5 ml ammonia water, and stir for 10 minutes. Disperse 0.4 ml of ethyl orthosilicate in 36 ml of alcohol and quickly add it to the single-necked flask. React at room temperature for 12 hours. Finally, wash with water and alcohol by centrifugation for 3 times, and store in alcohol for later use;

[0039] Separation of monodisperse PS@SiO2 beads

[0040] The PS@SiO2 ball suspension prepared as above is placed on a vibration-free workbench; after standing for a period of time, the upper solution and the lower precipitate in the suspension are removed; and monodispersed silica balls can be obtained by extracting the solution in the middle part.

[0041] Furthermore, 0.03g of PS microsphere powder was weighed and dissolved in a mixture of 35mL of anhydrous ethanol and 2mL of deionized water by ultrasonic dispersion. After the PS microspheres were completely dispersed, 0.5mL of ammonia water was quickly added to the system and reacted for 1h under continuous magnetic stirring. Subsequently, different amounts of tetraethyl orthosilicate were added to the system, and magnetic stirring was performed at room temperature (about 30°C in summer) for 8h to obtain a white solution. After centrifugation, water washing, alcohol washing, drying and other processes, white PS@SiO2 powder was obtained.

[0042] Through the self-assembly method, TTA-pdma was embedded in the surface of the hollow SiO2 crystal film, and then solidified by photopolymerization to obtain a photonic crystal with enhanced blue light emission.

[0043] Preparation and Sensitization Efficiency Determination of Photocatalyst CdS-Au

[0044] 2.21g BiCl3 and 1.05g CTAB were added to 60mL ethylene glycol, stirred vigorously for 40min, and then 2.8g Na3VO4 was added, stirred for 5min, and the mixture was added to a polytetrafluoroethylene hydrothermal reactor, and reacted at 160℃ for 3h. The product was washed with water and ethanol 3 times each, and dried in vacuum for 12h.

[0045] It has been tested that the hollow SiO2 photonic crystal embedded with TTA-PDMA can increase the Faraday efficiency of the photocatalyst CdS-Au from 40% to more than 90%.

[0046] Embodiment 2

[0047] 6 ml of styrene was used as a polymerization monomer, 0.5 ml of PVP was used as a comonomer, and the remaining steps were consistent with those in Example 1.

[0048] Embodiment 3

[0049] 7 ml of styrene was used as a polymerization monomer, 0.5 ml of PVP was used as a comonomer, and the remaining steps were consistent with those in Example 1.

[0050] Embodiment 4

[0051] 8 ml of styrene was used as a polymerization monomer, 0.5 ml of PVP was used as a comonomer, and the remaining steps were consistent with those in Example 1.

[0052] Embodiment 5

[0053] 9 ml of styrene was used as a polymerization monomer, 0.5 ml of PVP was used as a comonomer, and the remaining steps were consistent with those in Example 1.

[0054] The summary is shown in the following table:

[0055] Group Styrene (PS) PVP Embodiment 1 5ml 0.5ml Embodiment 2 6ml 0.5ml Embodiment 3 7ml 0.5ml Embodiment 4 8ml 0.5ml Embodiment 5 9ml 0.5ml

[0056] Since some acidic inhibitors are usually added to the stock of styrene and other monomers, they must be removed before use. The method is to put some clean cotton at the small opening at the bottom of a glass tube, then fill it with alumina sand, and then pour in styrene monomer to remove the inhibitor through the adsorption of alumina.

[0057] like Figure 1 As shown, through the FDTD transmission reflection simulation diagram analysis, it can be obtained that the photonic crystal band gap position of the sample should be 535nm, thereby confirming that the required SiO2 shell thickness is 20nm and the sphere diameter is 245nm.

[0058] like Figure 2 As shown, the five different sizes of PS beads with styrene amounts of 5, 6, 7, 8, and 9 ml prepared in all the examples can be observed through scanning electron microscopy images to show that the diameter of the beads gradually increases from 190 nm to 260 nm, as summarized in the following table:

[0059] Styrene (PS) Ball diameter (nm) 5ml 190 6ml 205 7ml 230 8ml 245 9ml 260

[0060] like Figure 3 As shown, the hollow SiO2 lens images obtained after sintering of each type of styrene-PVP were further tested. The test showed that the thickness of the sphere shell was 20nm, indicating that a suitable sphere structure was obtained.

[0061] At the same time Figure 4 Observation of the electron microscope images of PS, PS@SiO2, and hollow SiO2 spheres shows that they have good dispersion and are tightly packed.

[0062] Combination Figure 5 By analyzing the transmission spectra of PS spheres with different diameters, it can be seen that controlling the size of PS spheres can control the band gap position of the photonic crystal. The PS spheres with a styrene-PVP ratio of 8-0.5 are most consistent with the FDTD simulation results. At the same time, we prepared CdS-Au catalysts.

[0063] like Figure 6 As shown, the length of the synthesized nanorods tested in the lens image is 100 nm, and the longitudinal width of the rod is 3 nm, indicating that the cds nanorods have been successfully prepared.

[0064] Multiple groups of examples provided in this embodiment are analyzed by SEM images of five groups of PS beads of different diameters, and PS@SiO2 monodisperse colloidal particles are prepared by using silica prepared by the modified Stober method as a shell, thereby completing SiO2 encapsulation. Through high temperature treatment, a hollow SiO2 photonic crystal film is obtained. The photocatalyst CdS-Au is obtained, washed and dried. Through FDTD simulation, it is finally confirmed that the theoretical PS bead diameter is 245nm and the SiO2 shell thickness is 20nm. Through electron microscopy analysis, the PS bead with a styrene-PVP ratio of 8-0.5 is most consistent with the FDTD simulation results.

[0065] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a TTA photonic crystal, wherein the method utilizes the band edge effect of the photonic crystal to enhance the excitation light of TTA upconversion, thereby achieving structural enhancement of high-energy photons, characterized in that: First, PS beads with different ratios are prepared by soap-free emulsion polymerization, and then photonic crystals are prepared, including the following steps: Step S1: Gently place a magnetic stirrer in a reaction container, and add 0.1-1 g of initiator, 150 ml of deionized water, 5-9 ml of styrene as a polymerization monomer, and 0.5 ml of PVP as a comonomer in sequence; Step S2: Take a balloon with sufficient nitrogen for standby use, then build a complete reaction device with a magnetic stirrer and a reaction vessel, and connect the nitrogen balloon to the inlet of the reaction vessel through a nitrogen pipe, and adjust the nitrogen flow rate; Step S3: Turn on the magnetic stirring, set the temperature of the temperature controller at 30°C, stir with nitrogen for 30-45 minutes, then continue to heat up, set the temperature to 75°C, and close the gas outlet to prevent backflow; Step S4: After the temperature rises to 75°C, draw 5 ml of sample with a disposable syringe, add a small amount of quencher solution, record the color change of the reaction system, and stop heating after the reaction is carried out at 75°C for 5-8 hours; Step S5: performing magnetic stirring at room temperature to lower the system temperature to room temperature, and preparing five groups of PS beads with different styrene-PVP ratios; Step S6: modifying the prepared PS beads, preparing PS@SiO2 beads, and separating monodispersed PS@SiO2 beads, embedding TTA-pdma into the surface of the hollow SiO2 crystal film by self-assembly again, and then curing it by photopolymerization to obtain a photonic crystal with enhanced blue light emission; Step S7: Finally, the photocatalyst CdS-Au is prepared and the sensitization efficiency is measured with the photonic crystal.

2. The method for preparing a TTA photonic crystal according to claim 1, characterized in that: The reaction container is a clean 250 ml three-necked round-bottom flask; a thermometer is provided at one end of the three-necked round-bottom flask for measuring the oil bath temperature, so the set temperature is 3 to 5° C. higher than the reaction temperature.

3. The method for preparing a TTA photonic crystal according to claim 1, characterized in that: In step S2, the nitrogen pipe is immersed below the liquid level in the reaction container, and the nitrogen flow rate is adjusted to an appropriate flow rate so that the bubbling rate at the gas outlet is about 1-3 bubbles per second; a two-way valve is provided on the nitrogen pipe for controlling the gas flow rate.

4. The method for preparing a TTA photonic crystal according to claim 1, characterized in that: The magnetic stirring rate in step S3 is 300 rpm.

5. The method for preparing a TTA photonic crystal according to claim 1, characterized in that: The quencher solution used in step S4 is 0.5 ml of a 1.0 g / L hydroquinone aqueous solution.

6. The method for preparing a TTA photonic crystal according to claim 1, characterized in that: The styrene used in the preparation method will have some acidic inhibitors added due to inventory management requirements, so it must be removed before use, that is, using a glass tube, putting clean cotton at one end of the pointed outlet of the tube, then filling it with alumina sand, and then pouring in the styrene monomer that needs to be filtered.

7. The method for preparing a TTA photonic crystal according to claim 1, characterized in that: The obtained PS beads are modified, including the following steps: 10 ml of the PS beads obtained in step S5 are taken into a conical flask, 6 ml of ethanol is added, and 4 ml of 10 g / LPVPK30 alcohol solution is added under magnetic stirring, and the mixture is reacted at room temperature for 24 hours, and then the mixture is washed 6 times by alcohol centrifugation, and dispersed and stored in 9 ml of alcohol for later use.

8. The method for preparing a TTA photonic crystal according to claim 1, characterized in that: The preparation of PS@SiO2 beads includes the following steps: placing the prepared modified beads in a single-necked flask, adding 4.1 ml of ultrapure water and 0.5 ml of ammonia water, and stirring for 10 minutes; Take 0.4 ml of ethyl orthosilicate and disperse it in 36 ml of alcohol. Quickly add it to a single-necked flask and react it at room temperature for 12 hours. Finally, wash it by centrifugation with water and alcohol for 3 times and store it in alcohol for later use.

9. The method for preparing a TTA photonic crystal according to claim 1, characterized in that: The separation of monodisperse PS@SiO2 beads comprises the following steps: placing the PS@SiO2 bead suspension prepared as above on a vibration-free workbench; after standing for a period of time, removing the upper solution and lower precipitate in the suspension; and obtaining monodisperse silica beads by extracting the solution in the middle portion.

10. The method for preparing a TTA photonic crystal according to claim 1, characterized in that: The preparation of the photocatalyst CdS-Au includes the following steps: 2.21 g BiCl3 and 1.05 g CTAB are added to 60 mL ethylene glycol, stirred vigorously for 40 min, and then 2.8 g Na3VO4 is added, stirred for 5 min, and the mixture is added to a polytetrafluoroethylene hydrothermal reactor, and reacted at 160° C. for 3 h. The product is washed with water and ethanol 3 times each, and dried in a vacuum for 12 h.